2019
DOI: 10.1016/j.heliyon.2019.e02470
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella vulgaris supplementation effects on performances, oxidative stress and antioxidant genes expression in liver and ovaries of New Zealand White rabbits

Abstract: Oxidative stress is an exclusive biochemical complication affecting reproduction; hence, dietary antioxidant supplementation for its attenuation is a required nutrition – reproduction improvement strategy. On this background, Chlorella vulgaris (a natural antioxidant) was supplemented to grower female rabbits to maturity. The rabbits were thirty-five in number randomly distributed into five experimental groups in a completely randomized design. Control group was fed only basal feed while treatment groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 62 publications
3
23
0
1
Order By: Relevance
“…Glutathione peroxidase (GPX1) is an antioxidant gene increased due to the supplementation of essential oil or antibiotics. It was established that GPX1 reduces and detoxifies the hydrogen peroxide and organic hydroperoxides [ 91 ]. Thus, the up-regulation of this gene on the different groups could justify the reduction of the lipid peroxidation products in our study and reduce oxidative stress damages.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase (GPX1) is an antioxidant gene increased due to the supplementation of essential oil or antibiotics. It was established that GPX1 reduces and detoxifies the hydrogen peroxide and organic hydroperoxides [ 91 ]. Thus, the up-regulation of this gene on the different groups could justify the reduction of the lipid peroxidation products in our study and reduce oxidative stress damages.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress biomarkers including the malondialdehyde, protein carbonyl contents, total antioxidant capacity, and antioxidant enzyme activities of the liver and serum were determined using chemical assays as described in our previous studies [5].…”
Section: Determination Of Oxidative Stress Biomarkersmentioning
confidence: 99%
“…According to Christaki et al [4], microalgae generally can be considered as sources of minerals and complementary sources of protein and functional nutrients that are suitable for use in both animals and humans. Chlorella vulgaris as a functional food for humans, in addition to its regular nutritional composition of protein, carbohydrates, vitamins, and minerals, can provide healthpromoting benefits such as immune activation, antioxidant, anticarcinogenic, and also serving as an antitoxic agent [5]. In a bid to facilitate the understanding of the mechanisms of the antioxidant properties of the microalga Chlorella vulgaris, its effects on patterns of gene expression in rabbit models have been investigated and it was discovered to be capable of inhibiting the progression of oxidative stress via upregulation of antioxidant genes in the liver of rabbits [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the studies found were only focused on mammals. For example, Sikiru et al (2019) reported that C. vulgaris enhances oxidative stress, which was an exclusive biochemical complication that affected the reproduction in New Zealand White rabbits. Besides, the extract of C. vulgaris improves the histological adjustment of monosodium glutamate in ovarian tissue, the level of sex hormones, and increases the level of ovarian enzymatic antioxidants in adult female albino mice (Abdel-Aziem et al, 2018).…”
Section: Chlorella Vulgarismentioning
confidence: 99%